Combustion synthesis of TiO 2-Al-C/Al 2O 3 mixture in the presence of oxygen - Rahbari G, R.; Saw, L.H.; Hamdi, M.; Yahya, Rosiyah (2009)
Quasi-adiabatic combustion synthesis of optimized 3TiO 2+4Al+(3+x)C mixture in the presence of oxygen was carried out to produce TiC-Al 2O 3 composite. The influence of Al 2O 3 diluent in combusted (3TiO 2+4Al+3. 5C+yAl 2O 3) reactant mixture was investigated. Thermodynamics studies of the system shown that self-sustaining (SS) mode of combustion wave propagation can occur for large amounts of diluents (y = 2.5). Diluent reduced combustion temperature and rate of reaction kinetics. Oxide (Ti 2O, Ti 3O 5) and intermetallic (AlTi 2) phases were detected when extra Al 2O 3 was added to the mixture. Semi-quantitative XRD analysis was employed to study the phase formation of products for various amounts of diluent content in the mixture. The boundary between SS and non-SS modes of wave propagation was determined. Adding Al 2O 3 diluent slightly increased density that resulted in better thermal conductivity.